2006
DOI: 10.1038/modpathol.3800701
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable pathological characteristics in familial colorectal cancer with low-level microsatellite instability

Abstract: A high degree of microsatellite instability (MSI) in colorectal cancer (CRC) is a hallmark of hereditary nonpolyposis colorectal cancer (HNPCC), caused by germline defects in the mismatch repair (MMR) genes. A low degree of instability (less than 30% of the microsatellites) is seen in a subset of tumors. To clarify the significance of this low degree of MSI phenotype, we studied the differences between patients with colorectal tumors with high-level, low-level and no MSI. Colorectal tumors with no (n ¼ 68) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
2
5
1
Order By: Relevance
“…However, the reported prevalence varies according to ethnicity, number of markers, and the panels that were used for the MSI (Azzoni et al, 2011;Kets et al, 2006;Y. H. Kim et al, 2009;Mojarad et al, 2016;Rudzki et al, 2003), our results confirmed that tumors classified as MSI-L are a distinct molecular group with different clinicopathological features, however, other studies did not support the discrimination of MSI-L from MSS tumors in clinicopathological features (Kambara et al, 2001;S.…”
Section: Discussionsupporting
confidence: 70%
“…However, the reported prevalence varies according to ethnicity, number of markers, and the panels that were used for the MSI (Azzoni et al, 2011;Kets et al, 2006;Y. H. Kim et al, 2009;Mojarad et al, 2016;Rudzki et al, 2003), our results confirmed that tumors classified as MSI-L are a distinct molecular group with different clinicopathological features, however, other studies did not support the discrimination of MSI-L from MSS tumors in clinicopathological features (Kambara et al, 2001;S.…”
Section: Discussionsupporting
confidence: 70%
“…Families of late onset CRC with MSI-L or MSS exist (34). Therefore, it would be interesting to determine whether these families carry MSH3 germline mutations.…”
Section: Resultsmentioning
confidence: 99%
“…MSH3-deficiency is also associated with progression of disease (28, 35). MSI-L CRCs have poor clinical outcomes (34, 36, 37, 38), raising the possibility that MSH3-deficiency might contribute to metastasis in CRC. Certain genes containing di-, tri- or tetranucleotide repeats in their 5′ promoter, coding, and/or 3′ untranslated regions could be mutational targets of MSH3-deficiency, whose mutation might contribute to initiation or progression of tumors (38, 39).…”
Section: Resultsmentioning
confidence: 99%
“…This particular study focused on patients with stage I and II CRC. Several studies have examined MSI-high colorectal carcinomas and characterized both the number and phenotype of the tumor infiltrating cells [30, 31, 41, 43, 4749, 101, 102]. Studies by Smyrk et al described an increased level of tumor infiltrating lymphocytes (TILs) in CRCs with high levels of microsatellite instability.…”
Section: Increased Lymphocyte Infiltration Of Tumors In Lynch Syndmentioning
confidence: 99%